Effect of maintenance therapy with or without the use of chlorhexidine in teeth restored with composite resin in patients with diabetes mellitus - Nassar, Carlos Augusto; Serraglio, Ana Paula; Balotin, Anelize; Colte, Daniela; Camilotti, Veridiana; Busato, Priscilla de Monte Ribeiro; Spolidório, Luis Carlos [UNESP]; Nassar, Patricia Oehlmeyer (My University, 2011)
The objective of this study was to evaluate the effects of maintenance therapy with or without the use of 0.12% chlorhexidine in the periodontal tissues of patients with diabetes mellitus who had carious lesions restored with composed resin. Twenty patients were selected, all of whom had diabetes mellitus in addition to carious cervical lesions in previously treated teeth. After 90 days, improvement in plaque and gingival indices and probing depth were noticed among patients in the group that received 0.12% chlorhexidine.
Keywords: biomedical and dental materials; chlorhexidine; resin; topical antiinfective agent; adolescent; adult; aged; chemistry; classification; clinical trial; comparative study; controlled clinical trial; controlled study; dental caries; dental surgery; diabetes mellitus; human; methodology; middle aged; pathology; periodontal disease; periodontal pocket; periodontics; randomized controlled trial; tooth brushing; tooth cervix; tooth plaque; Adolescent; Adult; Aged; Anti-Infective Agents, Local; Chlorhexidine; Composite Resins; Dental Caries; Dental Materials; Dental Plaque; Dental Plaque Index; Dental Polishing; Dental Restoration, Permanent; Diabetes Complications; Humans; Middle Aged; Periodontal Diseases; Periodontal Index; Periodontal Pocket; Tooth Cervix; Young Adult